HUBUNGAN KEMANDIRIAN BELAJAR, GAYA BELAJAR DAN KEPERCAYAAN DIRI DENGAN HASIL BELAJAR PPKn - Subhan Syah; Aunurrahman Aunurrahman; Sulistyarini Sulistyarini (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThe aims of this research is to describe the relationship in: learning independence, learning style and self-co the independent variables to the dependent variable is. The form of this research is correlational. The correlational in this research uses a quantitative approach. The research was conducted at SD Negeri 25 Pontianak Timur with 28 students as sample. The data collection using questionnaire and instruments test. Data analysis with simple correlation technique and multiple correlation. The results showed that the positive and significant relationship between: 1) learning independence and Civics learning outcomes obtained r of 0.725. 2) learning style with Civics learning outcomes obtained r of 0.745. 3) self-confidence with PPKn learning outcomes obtained r of 0.527. 4) Learning independence and learning style with Civics learning outcomes obtained R of 0.801. 5) Learning independence and self-confidence with Civics learning outcomes obtained R of 0.731. 6) Learning style and selfconfidence with PPKn learning outcomes obtained R of 0.775. 7) Learning independence, learning style and self-confidence with PPKn learning outcomes obtained R of 0.805. 8) the total effective contribution of 64,8% consists of 25% contribution of the X1 variable (learning independence), 34.4% the contribution of the X2 variable (learning style) and 5.4% the contribution of the X3 variable (selfconfidence).Keywords: Learning Independence, Learning Style, Self-Confidence, PPKn Learning Outcomes